2022
DOI: 10.1111/jcmm.17241
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c‐Jun inhibits erastin‐induced ferroptosis in Schwann cells and promotes repair of facial nerve function

Abstract: Schwann cells (SCs), the myelin-forming cells of the peripheral nerve, play an important role in the repair process of nerve injury. 1 Currently, it is generally believed that SCs can reprogram to produce a cellular phenotype that promotes regeneration and repair after nerve injury, thus clearing excess myelin sheath, attracting macrophages, supporting the survival of damaged neurons, secreting various cytokines and guiding the growth of axons. 2 However, the normal performance of these roles needs enough SCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…JUN (formally known as c-JUN), a subunit of the activator protein 1 transcription factor, has multiple roles in determining ferroptosis sensitivity through either transcription-dependent or transcription-independent mechanisms (24). It has been reported that overexpression of JUN inhibits erastin-induced ferroptosis in Schwann cells (25). JUN is also deduced as a ferroptosis suppressor in the Ferroptosis Database, which is based on the study performed on human liver cancer cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…JUN (formally known as c-JUN), a subunit of the activator protein 1 transcription factor, has multiple roles in determining ferroptosis sensitivity through either transcription-dependent or transcription-independent mechanisms (24). It has been reported that overexpression of JUN inhibits erastin-induced ferroptosis in Schwann cells (25). JUN is also deduced as a ferroptosis suppressor in the Ferroptosis Database, which is based on the study performed on human liver cancer cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that c-Jun also downregulates p53, thereby inhibiting apoptosis. Recently, a growing number of research has indicated that c-Jun participates in the regulation of ferroptosis processes in some tumors [ 47 , 48 , 49 ]. Studies have shown that c-Jun can inhibit ferroptosis by stimulating GSH synthesis by increasing PSAT1 and CBS transcription [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (2021) pointed out complex IV subunit 4 isoform 2 (Cox4i2) can trigger an increase in reactive oxygen species, leading to ferroptosis and apoptosis in human herpesvirus 7 (HHV7) infected SCs. Gao et al (2022) found the overexpression of c-Jun, a key regulator of the response of SCs to peripheral nerve injury, inhibits erastininduced ferroptosis in SCs and promotes repair of facial nerve function.…”
Section: Neuropathic Pain Induced By Peripheral Nerve Injurymentioning
confidence: 99%
“…Several SCs-related studies have tried to clarify the mechanism of ferroptosis in peripheral nerve injury ( Chang et al, 2021 ; Gao et al, 2022 ). Chang et al (2021) pointed out complex IV subunit 4 isoform 2 (Cox4i2) can trigger an increase in reactive oxygen species, leading to ferroptosis and apoptosis in human herpesvirus 7 (HHV7) infected SCs.…”
Section: Introductionmentioning
confidence: 99%